A retrospective review of MVC's during the 2022 Festive season in Namibia - Ambunda, Paulus (Division of Emergency Medicine, 2025)
Introduction: Motor vehicle crashes (MVCs) are a public health concern and a major contributor to the morbidity and mortality of trauma patients globally. Morbidity and mortality from MVCs are forecasted to increase significantly by the year 2030. In 1998, MVCs were ranked as the 9th leading cause of global disease burden however this has risen to 3rd in 2020. Namibia is a SubSaharan country with a high number of MVCs however with limited epidemiological data. The study therefore aimed to describe the epidemiological characteristics of motor vehicle crashes in Namibia over a 1-month period during the 2022 festive season period. Methods: A descriptive observational study in the form of a retrospective review was conducted to describe the epidemiological characteristics of motor vehicle crashes in Namibia over 1 month period during the 2022 festive season period. The data was collected from the MVA Fund, a stateowned organisation, and analysed. The data was subjected to chi-square tests to determine association between variables and a geospatial analysis was done for the location data. Data was geocoded using the ESRI World Geocoder in ArcGIS Online. The data was subjected to cluster analysis and hotspot analysis. Results: A total of 292 crashes were included in the study with Khomas region recording the most (n=60). The majority of the crashes recorded, occurred in the evenings (18h01-21h00). No statistically significant differences were observed between the day of the week crashes occurred and the region in which they occurred (p-value=0.595). A statistically significant difference was however observed in the time of day the crashes occurred and the region (p-value= 0.046). A total of 87 patients were included from the 292 crashes. Of the 87 patients, 24 were female (27.6%) and 63 patients were male (72.4%). There were three fatalities. Females in the age group of 51-55 years were the most injured while males between 31-35 years were most injured. Fractures were the most common injury sustained. The total medical cost associated with management of these patients was over N$ 15 million over the study period. Conclusion: Young males are the majority of people involved in MVCs as found by our study and in line with global findings. The majority of individuals injured in crashes are within working ages and would be involved in the economic activities of the country. Injuries to these groups may have far-reaching socio-economic consequences. Lastly, MVCs over a month period alone carried a high cost and the annual cost of the medical management would be significant which may further negatively impact the country's economy. To curb the burden of crashes, interventions targeted specifically to the most affected population are required. Furthermore, the state of EMS in the crash clusters needs to be evaluated to identify any gaps. Identification of gaps could be used to strengthen EMS in these clusters and therefore lessen the trauma and mortality burden of crashes. It is well established in the literature that effective emergency care can alleviate most trauma morbidity and mortality.